Preparation and application of yolk-shell structure body phase hydrodesulfurization catalyst based on hydrogen overflow
By constructing auxiliary active phase with additional hydrogen activation capability and short-board 1T-MoS2 on the nanoscale, the problem of slow reaction rate of existing HDS catalysts when treating 4,6-DMDBT is solved, and the efficient hydrodesulfurization performance and ultra-deep desulfurization effect of the catalyst are achieved.
Patent Information
- Application Number
- CN202411726097.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When existing HDS catalysts treat large volume and large steric hindrance, the desulfurization effect is not significant, mainly due to the long migration path of MoS2 and active hydrogen in a single active phase, the reaction rate and the low active position utilization rate.
By constructing auxiliary active phases with additional hydrogen activation capacity on the nanoscale and using organic matter to inhibit the growth of sulfide crystal clusters, stable 1T-MoS2 with short-board long and low stacking is constructed to promote the transfer of active hydrogen.
The catalyst has achieved efficient hydrodesulfurization performance and high path selectivity, and can significantly reduce the sulfur content in the simulated oil under relatively mild reaction conditions, achieving ultra-deep desulfurization effect.
Smart Images

Figure CN119524885A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow, belonging to a non-loaded molybdenum-based catalytic material in the field of oil hydrogenation in industrial catalysis. Background Art
[0002] In recent years, with the in-depth exploitation of crude oil, its quality has become worse and worse. Crude oil with high sulfur content will produce a large amount of toxic gases when burned, causing serious harm to the environment and human health. In order to solve these problems, countries are actively developing various desulfurization methods to reduce the sulfur content in fuel oil. At present, hydrodesulfurization (HDS) technology has become an important means to produce ultra-low sulfur fuels due to its excellent desulfurization performance, high sustainability and low economic cost. Traditional HDS catalysts are usually used for direct desulfurization (DDS) of small molecular heterocyclic sulfides (such as thiophene, dibenzothiophene (DBT), etc.). However, the desulfurization effect of 4,6-dimethyldibenzothiophene (4,6-DMDBT) with large volume and large steric hindrance is not significant, making it one of the most difficult pollutants to degrade in fuel oil. The desulfurization process of 4,6-DMDBT is often completed by adsorbing the benzene ring plane on the catalyst and pre-hydrogenating and saturating to reduce steric hindrance (hydrogenation reaction (HYD) path). However, the current industrial HDS catalysts are mainly single-phase MoS2 with long plate length, and only the edge coordination unsaturated sites have catalytic activity for HDS, resulting in the restriction of adsorption sites and active hydrogen for the desulfurization of 4,6-DMDBT. Therefore, the fundamental method to achieve deep desulfurization depends on the design of HDS catalysts with abundant adsorption sites, especially those with additional hydrogen activation and migration capabilities.
[0003] In HDS system, NiS x (CoS x ) can act as an auxiliary active phase (donor) to activate H2 and provide hydrogen overflow (H so ), the acceptor phase (MoS2) receives the migrated H so And produce more unsaturated sulfur vacancies and -SH groups, thereby further improving the HDS activity and reaction path selectivity. Gil-Llambías et al. used γ-Al2O3 for physical separation and confirmed that CoS x or NiS x It has a promoting effect on MoS2, thereby improving the HDS activity of the catalyst (Appl. Catal. A Gen., 274 (2004) 303-309). Castillo-Villalon et al. studied the relationship between CoMoS and CoS by adjusting the ratio of Co / (Co+Mo) while keeping the number of CoMoS active sites basically unchanged. xThe synergistic effect of the two phases on the HDS activity resulted in a highly active HDS catalyst (Catal. Today, 394-396 (2022) 41-49). Therefore, the design of a multi-phase HDS catalyst with a hydrogen overflow effect can improve the hydrodesulfurization capacity of the traditional NiMoS / CoMoS with the assistance of additional active sites. However, the transfer of active hydrogen to the acceptor phase often requires a long distance, resulting in slow consumption of active hydrogen and reduced reaction rate. For example, Escalona et al. studied the interaction between Co9S8 and MoS x The effect of the distance between the donor and the acceptor on the synergistic effect was studied. The results showed that as the distance between the donor and the acceptor increased, the synergistic effect weakened, resulting in a decrease in the HDS catalytic efficiency. (Catal. Today, 282 (2017) 214-221). Therefore, constructing a catalyst with hydrogen overflow ability at the nanoscale, shortening the migration distance of active substances and increasing the types of active phases are of great significance for achieving ultra-deep hydrodesulfurization of oil products.
[0004] At present, relevant literature and patents report that yolk-shell nanoreactors have broad application prospects and great potential in HDS systems. Yolk-shell nanoreactors are nanomaterials that encapsulate particles in a hollow structure, which have strong thermal stability and adjustable pore size and shell thickness. The adjustable gaps in the yolk-shell structure not only expose more active sites for reactants, but also shorten the distance for the migration of active species. Chinese patent CN 116943678A discloses a method for preparing a yolk-shell structure phase hydrorefining catalyst. The invention uses soluble sodium salt as a raw material to improve the distribution state of active metals, increase the active center and dispersion of the catalyst, and improve the utilization rate and mechanical strength of the catalyst. Chinese patent CN116603564 A discloses a core-shell molecular sieve @ transition metal doping-molybdenum disulfide / carbon composite catalyst. The invention uses a ternary material synthesis method. The high dispersion of molybdenum species is achieved through the amino group in the positively charged polymer, thereby improving the utilization rate of metals. However, the catalysts prepared by the above schemes are all limited by the semiconductor properties and poor electron transport characteristics of traditional MoS2, which is not conducive to the transmission of active hydrogen, thereby reducing the rate of hydrodesulfurization reaction. Phase engineering plays a vital role in regulating the physicochemical properties of MoS2. Compared with the triangular prism structure of traditional 2H-MoS2, 1T-MoS2 adopts an octahedral coordination mode, which has unfilled empty orbitals near the Fermi level. Therefore, 1T-MoS2 exhibits higher electron transferability, which is beneficial to promote the transfer of active hydrogen in the HDS process and improve the HDS activity of the catalyst. Chinese patent CN 112316959A has confirmed that some intercalation molecules (such as those containing -OH) can enter MoS2 nanosheets and inject electrons into Mo 4d orbitals, which is expected to reduce the energy barrier from 2H to 1T, making the application of 1T-MoS2 in HDS reactions possible. At the same time, the presence of intercalated molecules prevents the excessive growth of MoS2 nanosheets, which is conducive to the production of short-plate length and low-stacking MoS2, thereby providing more "rim" sites and promoting the adsorption of 4,6-DMDBT. Therefore, the excellent structural characteristics of 1T-MoS2 constructed by molecular intercalation overcome the shortcomings of the 2H-MoS2 catalyst currently used in industry and promote the deep desulfurization of 4,6-DMDBT macromolecules.
[0005] However, the existing technology cannot simultaneously transfer the donor (NiS x or CoS x ), acceptors (NiMoS / CoMoS) and 1T-MoS2 are combined in the same nanoparticle, which limits the improvement of the activity, selectivity and stability of the HDS system catalyst. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow, so as to improve its hydrodesulfurization performance in oil refining. The catalyst solves the problems of slow reaction rate and low active site utilization caused by a single active phase and a long active hydrogen migration path by constructing an auxiliary active phase with additional hydrogen activation capacity at the nanoscale. Organic matter is used to inhibit the growth of sulfide crystal clusters and enter their intercalation, constructing a stable 1T-MoS2 with short plate length and low stacking, and promoting the transfer of active hydrogen. This catalyst exhibits excellent HDS performance and high path selectivity in oil refining, and is expected to become an important candidate material for ultra-deep desulfurization systems.
[0007] The first aspect of the present invention discloses a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow, wherein the mass percentage of Ni is 10-30wt.%, the mass percentage of Mo is 10-40wt.%, and NiMoS accounts for 20-90% of the total content of Ni species in the catalyst, and the Mo sulfide degree (Mo sulfidation %) is 40-80%.
[0008] The active phase MoS2 mainly exists stably as a 1T phase, with an average length of 0-6nm and an average number of stacking layers of 1-5. Based on the total number of stacking layers, the proportion of layers with 2-3 layers is 40-70%, preferably 40-70%.
[0009] The second aspect of the present invention discloses a technical solution for preparing the above-mentioned yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow as follows:
[0010] S1: Glycerol, isopropanol and deionized water are mixed uniformly in proportion and nickel nitrate hexahydrate is added, and a green transparent solution is obtained after stirring;
[0011] S2: Solvothermal reaction of the solution obtained in step S1 to obtain a solid spherical nickel composite precursor;
[0012] S3: mixing the nickel composite precursor obtained in step S2 and the ethanol solution of thioacetamide and stirring them evenly, adding an aqueous solution of ammonium molybdate to obtain a suspension;
[0013] S4: subjecting the suspension obtained in step S3 to a solvothermal reaction, washing and drying to obtain a yolk-shell structure catalyst;
[0014] Alternatively, the method comprises the following preparation steps:
[0015] S1: Glycerol, isopropanol and deionized water are mixed uniformly in proportion, nickel nitrate hexahydrate and molybdenum acetylacetonate are added, and a transparent solution is obtained after stirring;
[0016] S2: Solvothermal reaction of the solution obtained in step S1 to obtain a solid spherical nickel-molybdenum composite precursor;
[0017] S3: mixing the nickel-molybdenum composite precursor obtained in step S2 and the ethanol solution of thioacetamide and stirring them evenly, adding an aqueous solution of ammonium molybdate to obtain a suspension;
[0018] S4: subjecting the suspension obtained in step S3 to a solvothermal reaction, washing and drying to obtain a hollow structure catalyst.
[0019] Preferably, in step S1, the feed ratio of glycerol, isopropanol and deionized water is 5-9 mL: 45-60 mL: 0-2 mL; the mass ratio of nickel nitrate hexahydrate and molybdenum acetylacetonate is 0.06-0.1 g: 0-0.1 g.
[0020] Preferably, the temperature of the solvent thermal reaction in step S2 is 180-220° C. and the time is 8-12 h.
[0021] Preferably, in step S3, the mass ratio of the nickel composite precursor / nickel-molybdenum composite precursor, thioacetamide and ammonium molybdate is 0-0.05 g: 0.14-0.35 g: 0-0.25 g.
[0022] Preferably, the temperature of the solvent thermal reaction in step S4 is 180-220°C for 2-8h; or a two-step heating method: the first step is 100-150°C and maintained for 0-3h, and the second step is 180-220°C and maintained for 2-8h.
[0023] The third aspect of the present invention discloses the use of the above-mentioned yolk-shell structure phase catalyst based on hydrogen overflow in hydrodesulfurization.
[0024] Preferably, the yolk-shell structure phase catalyst based on hydrogen overflow is used for DBT and 4,6-DMDBT hydrodesulfurization at a temperature of 220-300° C. and a pressure of 4-6.5 MPa.
[0025] The working principle of the present invention is:
[0026] The catalyst is a novel confined sulfurization coupled in situ intercalation strategy, with a precisely designed nanoreactor with a stable yolk-shell structure for efficient hydrodesulfurization. The method involves a simple solvothermal synthesis of a nickel composite precursor. Subsequently, the Ni is slowly released by the Ostwald ripening effect. 2+ and glycerol to control the derivatization of 1T-MoS2 with abundant “rim” sites. This strategy has three advantages in regulating the structure of yolk-shell nanoreactors: (i) by slowly releasing Ni 2+, achieving controllable construction of NiMoS active sites at the atomic level, thereby improving the apparent activity of the catalyst. (ii) Through the coordination dissociation reaction of the nickel composite precursor, the in-situ intercalation of glycerol molecules is achieved at the molecular level, thereby constructing a stable 1T-MoS2. The high viscosity and high density of glycerol can increase the spatial resistance to the growth of the MoS2 core, thereby obtaining MoS2 with short plate length and low stacking, which is conducive to exposing more "rim" sites and improving the intrinsic activity of the catalyst. (iii) The confined sulfurization strategy controls the yolk-shell structure of the catalyst at the nanoscale, shortens the migration distance of active hydrogen, and improves the hydrodesulfurization reaction rate. The NiS2 core phase and the NiMoS shell layer have different functions in the HDS reaction, achieving a synergistic effect between multiple active phases. Therefore, the present invention not only provides a new method for the application of high-activity 1T-MoS2 in HDS, but also provides theoretical guidance for the rational design and controllable construction of efficient hydrogen overflow HDS catalysts.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) Gradual release of Ni through Ostwald ripening effect 2+ The NiMoS active phase is constructed, and the derivation and content of the active phase are controlled, thereby increasing the active material density of the catalyst.
[0029] (2) By utilizing the intercalation effect of glycerol, stable 1T-MoS2 nanosheets with short plate length and low stacking are derived and more edge sites are generated. The benzene ring in the 4,6-DMDBT molecule is adsorbed to the active center through planar adsorption, thereby carrying out the HYD path and improving the selectivity of the catalyst.
[0030] (3) The Mo-S bond energy of 1T-MoS2 is small, which is conducive to the breaking of Mo-S bonds to form new sulfur vacancies, thereby increasing the concentration of active centers for the HDS reaction.
[0031] (4) The unique structure of 1T-MoS2 in the catalyst has metallic properties, which greatly improves the conductivity of the catalyst, thereby increasing the electron migration rate on the catalyst surface and increasing the possibility of overflow hydrogen production.
[0032] (5) The voids in the yolk-shell structure not only expose more active sites for reactants but also provide a uniform environment for heterogeneous catalysis.
[0033] (6) The dense shell layer enables the catalyst to maintain its yolk-shell structure during the cyclic reaction, thus increasing the service life of the catalyst.
[0034] (7) The yolk-shell structure shortens the distance of active hydrogen migration at the nanoscale, facilitates the transfer and consumption of active hydrogen, and increases the reaction rate of HDS.
[0035] (8) The yolk-shell structure phase catalyst described in the present invention has the characteristics of simple operation, short production cycle and mild preparation conditions, which is of great significance for actual industrial production.
[0036] (9) The yolk-shell structure phase catalyst based on hydrogen overflow described in the present invention exhibits extremely high HDS activity and selectivity. Under relatively mild reaction conditions, the sulfur content in the simulated oil can be reduced from 500 ppm to below 10 ppm, thereby achieving ultra-deep desulfurization of the simulated oil. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The X-ray diffraction (XRD) diagrams of the catalysts prepared in the examples and comparative examples reflect the physical structures of the catalysts. In the sulfided catalysts of the present invention, the internal core phase is mainly NiS2, and the external shell is mainly NiMoS. Among them, the diffraction peaks of each catalyst at 2θ of 9.1°, 31.6° and 53.6° correspond to the (002) of the hexagonal 1T-MoS2 (PDF#01-089-2905) and the (200) and (311) crystal planes of the simple cubic NiS2 (PDF#00-011-0099), respectively, proving the successful preparation of the multiphase composite material. Since glycerol is inserted into the MoS2 layer, it can play a supporting and protective role, thereby increasing the MoS2 interlayer spacing so that it mainly exists in the 1T phase. Compared with other catalysts, the (002) crystal plane of H-Cat is offset at a high angle. This is because the nickel-molybdenum composite precursor lacks a large amount of Mo in the solution. 6+ , which makes the rigid shell of MoS2 form slowly, resulting in the loss of glycerol molecules and the formation of 2H phase.
[0038] Figure 2 The Raman spectra of the catalyst prepared in the example are further analyzed for the phase structure of the catalyst. Generally speaking, 146, 238, 283 and 336 cm -1 The characteristic peaks at belong to J1, J2, E of 1T-MoS2 1g and J3 vibration modes, while 379 and 402 cm -1 The characteristic peaks at 2H-MoS2 belong to E 1 2g and A 1gVibration mode. The comparison results show that YS-Cat-5h, MM-NiS2 / MoS2 and P-MoS2 have strong characteristic peaks of 1T-MoS2, while H-Cat mainly has characteristic peaks of 2H phase, which is consistent with the XRD analysis results. This shows that the glycerol released by the Ostwald ripening effect enters the MoS2 layer, causing the MoS2 lattice to transform into a 1T phase structure. Therefore, the controllable derivatization of the yolk-shell YS-Cat-5h catalyst using the confined sulfurization coupled in situ intercalation strategy can fully expose the active sites and form stable 1T-MoS2.
[0039] Figure 3 The scanning electron microscope (SEM) of the nickel composite precursor prepared in Example 1 Figure 3 a) Figure and SEM of yolk-shell structure phase hydrodesulfurization catalyst YS-Cat-5h ( Figure 3 b) Figure, transmission electron microscopy (TEM, Figure 3 c) Figure, high magnification transmission electron microscopy (HRTEM, Figure 3 d) Diagram and corresponding element distribution (Mapping) diagram ( Figure 3 e). The present invention controls the derivation of highly active transition metal sulfides by a self-sacrificial template method to construct a nanomaterial with a yolk-shell structure. According to the Mapping diagram, Ni, Mo and S elements are evenly distributed on the YS-Cat-5h catalyst. Among them, Mo only exists on the outer shell of YS-Cat-5h, while Ni exists in the inner core and the outer shell at the same time. Combined with the XRD results, it can be seen that the YS-Cat-5h catalyst is a yolk-shell nanosphere composed of a Ni-doped MoS2 outer shell (NiMoS) and a NiS2 inner core. In addition, since glycerol limits the growth of MoS2 and the strong reducibility of thioacetamide induces more crystal nuclei, MoS2 crystal clusters with short plate length and few stacking numbers are derived. The core phase NiS2 inside the catalyst produces active hydrogen, which is transferred to the outer shell NiMoS and derives more unsaturated sulfur vacancies and -SH groups, thereby improving the HDS activity of the catalyst and the path selectivity of the reaction, and realizing ultra-deep desulfurization of oil products.
[0040] Figure 4 is the SEM of each sulfided catalyst prepared in Comparative Examples 1, 2, 3 and 4 ( Figure 4 ad) and TEM images ( Figure 4 eh), in the early stage of the sulfurization reaction, TAA is decomposed at high temperature to produce S 2- Ni released from ions and nickel composite precursor 2+ and Mo in solution 6+ The reaction generates a rigid NiMoS shell around the nickel composite precursor nanospheres, while the Ni 2+The surrounding glycerol molecules are retained in the MoS2 nanosheets. The continuous dissipation of the nickel composite precursor during the further sulfurization process causes the core phase to gradually shrink and the shell to gradually thicken. 2+ and S 2- The different diffusion rates of Ni lead to a significant gap (100 nm) between the shell and the core, which resulted in a yolk-shell nanoreactor with fully exposed active sites. 2+ All with Mo in solution 6+ and S 2- The reaction results in the loss of the NiS2 core and the formation of hollow spheres. Thus, Ni is gradually released through the Ostwald ripening effect. 2+ , promoting Ni 2+ It is converted into the active phase NiMoS to the greatest extent and constructs the auxiliary active phase NiS2 core to improve the HDS activity of the catalyst.
[0041] Figure 5 SEM images of the solid spherical nickel-molybdenum composite precursor and the catalysts prepared in Examples 3, 4, and 5 ( Figure 5 a) and TEM images ( Figure 5 bd), compared with Example 1, the solid spherical nickel-molybdenum composite precursor directly generated a hollow structure catalyst ( Figure 5 b) This indicates that a large amount of Mo in the solution is missing. 6+ The presence of , it is difficult to ensure the rapid formation of the rigid shell of MoS2, resulting in the loss of various components of the catalyst, which is not conducive to the generation of hydrogen overflow effect. In addition, P-MoS2 self-assembles into dandelion-shaped nanosheets to reduce the surface energy ( Figure 5 c), and it only exists in the form of single-phase MoS2. The MM-NiS2 / MoS2 catalyst obtained by uniformly mixing NiS2 and MoS2 through mechanical grinding has nanosheets agglomerated and intertwined ( Figure 5 d), which will be detrimental to the exposure of active sites in the HDS reaction. Therefore, the YS-Cat-5h catalyst with a yolk-shell structure was controllably constructed using the Ostwald ripening effect, which can provide a short-distance (100nm) hydrogen overflow path for the HDS reaction and construct an HDS nanoreactor.
[0042] Figure 6The HDS reaction network of DBT and 4,6-DMDBT, the main products of which are tetrahydrodibenzothiophene (THDBT), hexahydrodibenzothiophene (HHDBT), biphenyl (BP), cyclohexylbenzene (CHB), 3,3′-dimethylbiphenyl (3,3′-DMBP), 3,3′-dimethylbicyclohexane (3,3′-DMBCH), 3,3′-dimethylcyclohexylbenzene (3,3′-DMCHB), 4,6-hexahydrodimethyldibenzothiophene (4,6-HHDMDBT) and 4,6-tetrahydrodimethyldibenzothiophene (4,6-THDMDBT). Taking DBT as an example, in the DDS pathway, the CS bond is first broken to generate BP. In the HYD pathway, one benzene ring of DBT is first saturated with H2 to generate THDBT and HHDBT, and then the CS bond is cleaved, and the final product is CHB. The HDS reaction of 4,6-DMDBT also includes two parallel reaction pathways: one is the DDS pathway, that is, the CS bond in 4,6-DMDBT is first broken to generate 3,3′-DMBP, 3,3′-DMBP is partially hydrogenated to generate 3,3′-DMCHB, and further hydrogenated to generate 3,3′-DMBCH; the other is the HYD pathway, that is, a benzene ring in 4,6-DMDBT is first partially hydrogenated to generate 4,6-THDMDBT and 4,6-HHDMDBT, and then the CS bond is broken to generate 3,3′-DMCHB, or further hydrogenated to generate 3,3′-DMBCH. The ratio of the total concentration of the HYD pathway products to the total concentration of the DDS pathway products is used to represent the pathway selectivity.
[0043] Figure 7 The HDS performance and selectivity analysis diagram of each catalyst in the comparative example. The horizontal axis represents the duration of the solvent thermal reaction stage during the catalyst preparation process, and the vertical axis represents the performance parameters during the hydrodesulfurization catalytic process. The 4,6-DMDBT conversion rate shows an inverted U-shaped curve as the solvent thermal time increases. This is because the Ni composite precursor slowly releases Ni in the initial stage of sulfurization. 2+ With the large amount of Mo in the solution 6+ and S 2- The NiMoS shell is formed by reaction. As the solvothermal reaction proceeds, the nickel composite precursor continues to decompose and the sample sulfidation degree and NiMoS content gradually increase. When the reaction reaches a certain stage, the nickel composite precursor is completely consumed and NiMoS begins to decompose into two phases, resulting in a decrease in the sulfidation degree and NiMoS content of the catalyst, thereby reducing the 4,6-DMDBT conversion rate. In addition, S HYD / DDSIt also has a similar trend to the conversion rate, which is because the length of the MoS2 plate and the number of stacking can be controlled by adjusting the sulfurization time. Short and low-stacked MoS2 sheets have more edge coordination unsaturated sites, which is conducive to more Ni atoms entering the edge positions of MoS2, promoting the adsorption and dissociation of molecular hydrogen into active hydrogen, thereby improving the selectivity of the HYD reaction. Therefore, the controllable construction of yolk-shell catalysts using the Ostwald ripening effect can reasonably adjust the content of NiS2 and NiMoS, promote the full utilization of each phase, and thus improve the HDS activity of the catalyst.
[0044] Figure 8 This is a method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow and its mechanism of application in hydrogenation reactions. Through confined sulfurization coupled with an in-situ intercalation strategy, the effects of the catalyst's morphology, chemical composition and other physical and chemical properties on hydrogenation activity and path selectivity can be controlled. This effect is mainly attributed to the control of the intercalation molecules on the active phase content and the number of stacking layers, which makes the catalyst have a high multiphase synergistic effect. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the embodiments and drawings, but the protection scope of the present invention is not limited to the embodiments.
[0046] In the following examples, unless otherwise specified, the materials, reagents, etc. used were all purchased from conventional commercial products in the field, and the methods, operations, etc. used were all conventional technical means in the field.
[0047] A yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow, the catalyst has a core phase structure and a shell layer structure. The core phase is NiS2, the shell layer is NiMoS phase (Ni-MoS2), wherein the mass percentage of Ni is 10-30wt.%, the mass percentage of Mo is 10-40wt.%, and NiMoS accounts for 20-90% of the total content of Ni species in the catalyst, and the Mo sulfide degree (Mo sulfidation The MoS2 mainly exists in a 1T phase, with an average length of 0-6nm and an average number of stacking layers of 1-5. Based on the total number of stacking layers, the proportion of 2-3 layers is 40-70%, preferably 40-70%.
[0048] Example 1
[0049] (1) 145 mg of nickel nitrate hexahydrate was dissolved in a mixed solution of 7.50 mL of glycerol and 52.5 mL of isopropanol, and 1 mL of deionized water was added. The mixture was stirred at 800 rpm for 40 min, and then the solution was transferred to a 200 °C reactor and kept for 10 h. After cooling to room temperature, the product was collected by centrifugation to obtain a solid spherical nickel composite precursor.
[0050] (2) First, 0.050 g of nickel composite precursor was ultrasonically dispersed in 10 mL of ethanol to obtain a uniform solution. Next, 15 mL of thioacetamide (0.244 g) in ethanol solution was added thereto and stirred for 20 min. Then 15 mL of ammonium heptamolybdate (0.143 g) aqueous solution was added and stirred for 10 min. The mixed solution was transferred to a reactor and reacted at 200 °C for 5 h. The black precipitate was collected by centrifugation to obtain the yolk-shell structure catalyst YS-Cat-5h.
[0051] Example 2
[0052] (1) 145 mg of nickel nitrate hexahydrate was dissolved in a mixed solution of 7.50 mL of glycerol and 52.5 mL of isopropanol, and 1 mL of deionized water was added. The mixture was stirred at 800 rpm for 40 min, and then the solution was transferred to a 200 °C reactor and kept for 10 h. After cooling to room temperature, the product was collected by centrifugation to obtain a solid spherical nickel composite precursor.
[0053] (2) First, 0.050 g of the nickel composite precursor was ultrasonically dispersed in 10 mL of ethanol to obtain a uniform solution. Then, 15 mL of thioacetamide (0.244 g) in ethanol was added and stirred for 20 min. The mixed solution was transferred to a reactor and reacted at 200 °C for 5 h. The black precipitate was collected by centrifugation to obtain the catalyst P-NiS2.
[0054] Example 3
[0055] 0.143 g of ammonium heptamolybdate was ultrasonically dispersed in 10 mL of deionized water to obtain a uniform solution. 15 mL of thioacetamide (0.244 g) in ethanol solution was added thereto and stirred for 20 min. The mixed solution was transferred to a reactor and reacted at 200 ° C for 5 h. The black precipitate was collected by centrifugation to obtain the catalyst P-MoS2.
[0056] Example 4
[0057] Equimolar amounts of P-MoS2 and P-NiS2 were mechanically ground to obtain the catalyst MM-NiS2 / MoS2.
[0058] Example 5
[0059] This example provides a method for preparing a hollow structure phase hydrodesulfurization catalyst, including an outer coating shell layer of the catalyst prepared in Example 1.
[0060] (1) 0.080 g of molybdenum acetylacetonate and 0.080 g of nickel nitrate hexahydrate were dissolved in a mixed solution of 7.50 mL of glycerol and 52.5 mL of isopropanol, and 1 mL of deionized water was added. The mixture was stirred at 800 rpm for 40 min, and then the solution was transferred to a 200 ° C reactor and kept for 10 h. After cooling to room temperature, the product was collected by centrifugation to obtain a solid spherical nickel-molybdenum composite precursor.
[0061] (2) First, 0.050 g of nickel-molybdenum composite precursor was ultrasonically dispersed in 10 mL of ethanol to obtain a uniform solution. Next, 15 mL of thioacetamide (0.244 g) in ethanol was added and stirred for 20 min. Then 15 mL of ammonium heptamolybdate (0.143 g) aqueous solution was added and stirred for 10 min. The mixed solution was transferred to a reactor and reacted at 200 ° C for 5 h. The black precipitate was collected by centrifugation to obtain a hollow structure catalyst H-Cat.
[0062] Comparative Example 1
[0063] The synthesis process is basically the same as that in Example 1, except that the reaction time in the reactor in step (2) is changed to 2 h. Other conditions are the same as those in Example 1, and catalyst YS-Cat-2h is obtained.
[0064] Comparative Example 2
[0065] The synthesis process is basically the same as that in Example 1, except that the reaction time in the reactor in step (2) is changed to 4 h. Other conditions are the same as those in Example 1 to obtain catalyst YS-Cat-4h.
[0066] Comparative Example 3
[0067] The synthesis process is basically the same as that in Example 1, except that the reaction time in the reactor described in step (2) is changed to 6 hours. Other conditions are the same as those in Example 1 to obtain catalyst YS-Cat-6h.
[0068] Comparative Example 4
[0069] The synthesis process is basically the same as that in Example 1, except that the reaction time in the reactor in step (2) is changed to 8 h. Other conditions are the same as those in Example 1, and catalyst YS-Cat-8h is obtained.
[0070] Table 1 XPS data of catalysts prepared in Examples and Comparative Examples
[0071]
[0072] a :Mo sulfidation % = Mo 4+ Area%÷(Mo 4+ Area%+Mo 5+Area%+Mo 6+ Area %)
[0073] b :[NiMoS]%=NiMoS Area%÷(Ni x S y Area%+NiMoS Area%+Ni 2+ Area %)
[0074] Table 2 Elemental analysis results of catalysts prepared in Examples and Comparative Examples
[0075]
[0076] Application Example 1
[0077] The performance of each catalyst was evaluated using a DBT n-decane solution with a sulfur content of 500 ppm as simulated oil. The hydrodesulfurization of DBT was carried out in a 100 mL batch reactor, with a reaction pressure of 6 MPa, a reaction temperature of 300 ° C, a reaction time of 4 h, a catalyst dosage of 50 mg, and a reaction liquid volume of 30 mL. The evaluation results of each catalyst are shown in Table 3.
[0078] Table 3 HDS activity and product distribution of catalysts of different embodiments for DBT
[0079]
[0080]
[0081] a The DBT conversion was about 50%.
[0082] Application Example 2
[0083] The performance of each catalyst was evaluated using a 4,6-DMDBT n-decane solution with a sulfur content of 500 ppm as simulated oil. The hydrodesulfurization of 4,6-DMDBT was carried out in a 100 mL batch reactor, with a reaction pressure of 6 MPa, a reaction temperature of 300 ° C, a reaction time of 4 h, a catalyst dosage of 50 mg, and a reaction liquid volume of 30 mL. The evaluation results of each catalyst are shown in Tables 4 and 5.
[0084] Table 4 HDS activity and product distribution of catalysts of different embodiments for 4,6-DMDBT
[0085]
[0086] a Measured when the conversion of 4,6-DMDBT is about 50%
[0087] Table 5 HDS activity and product distribution of different comparative catalysts for 4,6-DMDBT
[0088]
[0089] From the table above, it can be seen that the HDS activity and HYD selectivity of catalyst YS-Cat-5h are much higher than those of other catalysts. This is because the slow release of glycerol under the Ostawald ripening effect increases the solvent resistance during the sulfidation process, resulting in the growth of MoS2 being limited by mass transfer. TAA has strong reducing properties and can induce more MoS2 nuclei, which ultimately leads to shorter plate lengths and lower stacking layers of MoS2 nanosheets, thereby producing more "rim" sites. The benzene rings in the 4,6-DMDBT molecule can be adsorbed on the active center through the plane, thereby promoting the HYD reaction. In addition, the yolk-shell structure constructed at the nanoscale has a hydrogen overflow effect. The inner core NiS2 can activate hydrogen as an additional active site and overflow to the outer shell NiMoS phase. The electron-rich 1T-MoS2 can assist the transfer of active hydrogen and promote the hydrogen overflow effect, so the ultra-deep hydrodesulfurization of oil products is achieved through multi-phase synergy.
[0090] The above embodiments are only used to help understand the core ideas and methods of this application. For those skilled in the art, appropriate modifications can be made to this application without departing from the application and the working principle, and these modifications also fall within the scope of protection of the claims of this application.
Claims
1. A yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow, characterized in that: The catalyst consists of an internal core phase and an external shell layer; the internal core phase is a NiS2 phase, the external shell layer is a NiMoS phase (Ni-MoS2), and the shell layer thickness is no more than 1 / 3 of the catalyst radius.
2. The yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 1, characterized in that: The MoS2 in the shell layer exists stably in the 1T phase. The interlayer spacing of MoS2 is increased by organic matter and small-scale MoS2 is controllably derived, with an average length of 0-6nm and an average number of stacking layers of 1-5. Based on the total number of stacking layers, the proportion of 2-3 layers is 40-70%, preferably 40-70%.
3. The yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 1, characterized in that: The mass percentage of Ni is 10-30wt.%, the mass percentage of Mo is 10-40wt.%, and NiMoS accounts for 20-90% of the total Ni content of the catalyst. sulfidation %) is 40-80%.
4. A method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow as described in claims 1-3, characterized in that: The steps include: S1: Glycerol, isopropanol and deionized water are mixed uniformly in proportion and nickel nitrate hexahydrate is added, and a green transparent solution is obtained after stirring; S2: Solvothermal reaction of the solution obtained in step S1 to obtain a solid spherical nickel composite precursor; S3: mixing the nickel composite precursor obtained in step S2 and the ethanol solution of thioacetamide and stirring them evenly, adding an aqueous solution of ammonium heptamolybdate to obtain a suspension; S4: subjecting the suspension obtained in step S3 to a solvothermal reaction, washing and drying to obtain a yolk-shell structure catalyst; Alternatively, the method comprises the following preparation steps: S1: Glycerol, isopropanol and deionized water are mixed uniformly in proportion, nickel nitrate hexahydrate and molybdenum acetylacetonate are added, and a transparent solution is obtained after stirring; S2: Solvothermal reaction of the solution obtained in step S1 to obtain a solid spherical nickel-molybdenum composite precursor; S3: mixing the nickel-molybdenum composite precursor obtained in step S2 and the ethanol solution of thioacetamide and stirring them evenly, adding an aqueous solution of ammonium heptamolybdate to obtain a suspension; S4: subjecting the suspension obtained in step S3 to a solvothermal reaction, washing and drying to obtain a hollow structure catalyst.
5. The method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 4, characterized in that: In step S1, the feed ratio of glycerol, isopropanol and deionized water is 5-9 mL: 45-60 mL: 0-2 mL; the mass ratio of nickel nitrate hexahydrate and molybdenum acetylacetonate is 0.06-0.1 g: 0-0.1 g.
6. The method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 4, characterized in that: The temperature of the solvent thermal reaction in step S2 is 180-220° C. and the time is 8-12 hours.
7. The method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 4, characterized in that: In step S3, the mass ratio of the nickel composite precursor / nickel-molybdenum composite precursor, thioacetamide and ammonium heptamolybdate is 0-0.05g: 0.14-0.35g: 0-0.25g.
8. The method for preparing a yolk-shell structure phase hydrodesulfurization catalyst based on hydrogen overflow according to claim 4, characterized in that: The temperature of the solvent thermal reaction in step S4 is 180-220°C and the time is 2-8h; or a two-step heating method: the first step is 100-150°C and maintained for 0-3h, and the second step is 180-220°C and maintained for 2-8h.
9. Use of the yolk-shell structure phase catalyst based on hydrogen overflow as claimed in claims 1 to 3 in hydrodesulfurization.
10. The use of a yolk-shell structure phase catalyst based on hydrogen overflow according to claim 9, characterized in that: The yolk-shell structure phase catalyst is used for the hydrodesulfurization of dibenzothiophene and 4,6-dimethyldibenzothiophene at a temperature of 220-300° C. and a pressure of 4-6.5 MPa.
Citation Information
Patent Citations
Nickel sulfide nanometer powdered material with aluminium sulfide casing and preparation method thereof
CN104386766A
Preparation method for preparing 1T-2H MoS2 with mixed morphology through solvothermal method and application of 1T-2H MoS2
CN114887631A
Production process of a core / shell structured solid support metal catalyst
EP2985079A1
Cited By
A core-shell structure catalyst for hydrogenation of waste plastic cracking oil, a preparation method and application thereof
CN122682627A